Death Involving Chloroquine: Analytical Aspects† - SARIN, R.K.; SATPATHY, K.P.; RAMTEKE, V.B.; SAMIKANNU, P.; P. SHARMA, GYAN (Asian Journal of Chemistry, 2010)
An unusual death is described where the deceased, a foreigner in a closed room ingested a large quantity of chloroquine. The circumstances, autopsy findings and laboratory identification of chloroquine are described and the levels ot chloroquine in the viscera are interpreted as the cause of death.